Vibrational spectroscopy of thin film condensates of ethanol mixture with inert gase - Aldiyarov, A.U.; Sokolov, D.Y.; Tychengulova, A.Z.; Yerezhep, D. (Recent Contributions to Physics, 2021)
It is known that by changing the concentration in an inert medium, it is possible to form clusters of various sizes of any substance by condensing them on a cold substrate from the gas phase. Traditionally, such systems are presented by molecular cryocrystals. This paper demonstrates the results of IR spectrometric studies of cryovacuum condensates of ethanol mixture with nitrogen. The main task of this study is to explain the complex, most often, ambiguous behavior of thin films of ethanol cryovacuum condensates in the process of its co-condensation with nitrogen. For this purpose, vibrational spectroscopy of cryodeposited thin films of "ethanol in nitrogen" mixtures in various concentration ratios was performed. The objects of research are thin films of cryocondensates of ethanol mixture with inert gas (N2). The samples were condensed at the temperature T = 16 K. The pressure of the gas phase of the mixture during cryocondensation was kept at P = 10-5 Torr. The range of ethanol concentrations in the mixtures varied from 3% to 90%. The spectral range of measurements was considered in 400-4200 1/cm. It is assumed that the change in the concentration of ethanol in the mixture leads to the formation of various cluster compositions of ethanol molecules dissolved in an inert medium.